User Expectation of Public Transport Design Experience for Electric Bike Sharing in Indonesia - Yukhi Mustaqim Kusuma Syabana; Kadek Heri Sanjaya; Gun Bae Park; Arief Suryadi Satyawan (Journal of Visual Art and Design, 2021)
Recently, Indonesia has been rapidly developing public transport infrastructure. However, many people still prefer using a private vehicle for their daily mobility. This study explored the design direction of an electric bike sharing system (EBS) for the first mile/last mile (FMLM) as part of an integrated public transport system to attract more people to public transportation. A focus group interview (FGI) was performed with ten Indonesian students currently studying at Daegu City, South Korea. All of them had experience using public transportation in both Indonesia and South Korea. From the FGI, the data on user needs related to FMLM was analyzed to understand the gap between expectations and reality as well as to enhance the feasibility of the design and development of EBS. In the next stage, based on the various needs and expectations of the participants about ideal public transportation in Indonesia, design strategies and elements were achieved and optimized specifically for EBS. Furthermore, we propose two usability scenarios in order to meet the user requirements. This study will be proposed to traffic policymakers for use in developing a design strategy and direction for an eco-friendly EBS formulation.